1991
DOI: 10.1128/jvi.65.11.6343-6348.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a retinoic acid-inducible endogenous retroviral transcript in the human teratocarcinoma-derived cell line PA-1

Abstract: Retinoic acid (RA), a developmental morphogen, causes activation of a transcript of an endogenous retrovirus-related element in the human teratocarcinoma-derived cell line PA-1. This provirus is defective, and the provirus-related sequences exist as multicopy elements (more than 20 copies) in human DNA. This is the first human endogenous retroviral mRNA that is known to be transcriptionally activated by RA. The nucleotide sequence of the 3,357 bp of this viral cDNA was determined and shows a strong homology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The inhibitory effect of AtRA on the expression of the E7 oncogene was due to suppression of the HPV16 promoter (p97) (Faluhelyi et al, 2004). In the present study, AtRA treatment significantly increased transcription of both Sp1 and L1 genes, which is similar to a previous report that AtRA activates transcription of an endogenous retrovirus‐related element in the human teratocarcinoma‐derived cell line PA‐1 (Kannan et al, 1991). Conversely, AtRA blocked the translation of Sp1 and L1 proteins, revealing that AtRA differentially regulates transcription and translation of both Sp1 and L1 genes in the primary KC cultures.…”
Section: Discussionsupporting
confidence: 92%
“…The inhibitory effect of AtRA on the expression of the E7 oncogene was due to suppression of the HPV16 promoter (p97) (Faluhelyi et al, 2004). In the present study, AtRA treatment significantly increased transcription of both Sp1 and L1 genes, which is similar to a previous report that AtRA activates transcription of an endogenous retrovirus‐related element in the human teratocarcinoma‐derived cell line PA‐1 (Kannan et al, 1991). Conversely, AtRA blocked the translation of Sp1 and L1 proteins, revealing that AtRA differentially regulates transcription and translation of both Sp1 and L1 genes in the primary KC cultures.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, enhanced expression of ERV-3 appears to be related to higher cellular differentiation as observed in a human monoblast cell line exposed to retinoic acid or vitamin D3 [92]. Kannan et al [93] found that retinoic acid could cause the activation of a transcript of another HERV, RRHERV-I, in the human teratocarcinoma-derived cell line PA-1.…”
Section: Vitaminsmentioning
confidence: 94%
“…Of the positive SLE patients, eight had antibody to the Sn nucleoprotein. These authors reported (180) that the proline-rich epitope shared by Sn and p24 of HIV-1 represented 88 URNOVITZ AND MURPHY CLIN. MICROBIOL.…”
Section: Hervs and Autoimmune Diseasementioning
confidence: 99%